The Effect of Propolisâ Ethanolic Extract on Serum Malondialdehyde level of mice Balb/c induced by cigarette smoke - Putra, Riyan Angga; Prasetyo, Diding Heri; Pesik, Riza Novierta (Nexus Biomedika, 2015)
Background: Propolis ethanolic extract contains many kind of potent antioxidant substances, such as resveratrol, chrysin and caffeic acid in abundant quantities. These cause Propolis owns prosperity to be antioxidant and antiinflamation agent which are able to fight against free radical effect of cigarette smoke, thus lipid peroxidation wont exist and the Malondialdehyde (MDA) formation can be banned. The objective of this research was to prove the effect of Propolis ethanolic extract on serum MDA level of mice balb/c which were induced by cigarette smoke. Methods: This was a laboratory experimental research the post test only control group design. Samples were twenty five mice, Swiss webster type (age 6-8 weeks; weight 20-30 gram) divided into 5 groups, each group had five mice. Mice for Control Group (KK) and Induction Group (KI) were administered by distilled water. While, the First Treatment Group (KP1), the Second Treatment Group (KP2) and the Third Treatment Group (KP3) were administered Propolis ethanol extract by dose 5.6 mg, 11.2 mg and 16.8 mg per 20 g of body weight of mice respectively. All groups except KK, were induced by smoke of one cigarette stick per day before extract administration. This research was done for 14 days. On day 15th, all mice were sucked the blood, then the MDA level were measured. The data were analyzed by using One-Way ANOVA (α = 0.05) and continued by Post Hoc test (α = 0.05). Results: The results of One-Way ANOVA test showed that there was significant difference among four-groups. Post Hoc test results showed there was significant difference among all groups. Conclusion: The administration of Propolis ethanolic extract of dose 5.6 mg/20 g of body weight of mice can decrease the serum malondialdehyde level of mice Balb/c which are induced by cigarette smoke significantly. Keywords: Propolis, Cigarette smoke, Malondialdehid level